Molecular analysis and new records of the invasive polychaete Boccardia proboscidea (Annelida: Spionidae) - VASILY I. RADASHEVSKY; VICTORIA V. PANKOVA; VASILY V. MALYAR; TATYANA V. NERETINA; ROBIN S. WILSON; TIM M. WORSFOLD; MARÍA E. DIEZ; LESLIE H. HARRIS; STÉPHANE HOURDEZ; CÉLINE LABRUNE; CÉLINE HOUBIN; BRITTA KIND; et al. (Mediterranean Marine Science, 2019)
The spionid polychaete Boccardia proboscidea Hartman, 1940 is a tube-dweller and shell/stone-borer widely occurring in temperate waters across the world and considered invasive in many areas. It was originally described from California, USA, and later reported from Pacific Canada, the Asian Pacific, Australia, New Zealand, Argentina, South Africa, and northern Europe. The Bayesian inference analysis of sequence data of three gene fragments (836 bp in total) of the mitochondrial 16S rDNA, nuclear 28S rDNA, and Histone 3 has shown that individuals from the Pacific coasts of Canada and the USA, Argentina, Australia, South Africa, the United Kingdom, and Mediterranean France were genetically very similar (maximal average p-distance value, 0.49%, was between 16S rDNA sequences). We consider these individuals to be conspecific and report the earliest records of B. proboscidea from the UK and a possible first Mediterranean record in the Gulf of Lion. The high 16S haplotype diversity of B. proboscidea detected in the north-eastern Pacific suggests a native distribution for the species in the northern Pacific and subsequent introductions through human activities to other parts of the world. The histories of these introductions are reviewed and the hypotheses about times and places of introductions are updated.